ANALISIS MODEL-MODEL PENDAYAGUNAAN DANA ZAKAT DALAM PEMBERDAYAAN MASYARAKAT MISKIN KOTA DI PROVINSI LAMPUNG - Nedi Hendri; Suyanto Suyanto (Akuisisi: Jurnal Akuntansi, 2015)
The problems of poverty are quite complex requiring the intervention of all parties. Most of Zakat Management Organization run the utilization program of zakat to tackle the problem of poverty only by its own logic. Therefore the empowerment models of  Zakat funds to the urban poor in different system, with the advantages and disadvantages of each system. The aim of this study is to find a prototype model of the proper optimization of charity funds in the empowerment of the poor town based on local wisdom in Lampung province. For the first stage this study used a survey method with the data derived from the results of the Focus Group Discussion (FGD) and in-depth interviews with the speakers is the model identification stage. In the second stage is the stage of reconstruction model using comparative analysis.Community Based Development is a method of approach that involves communities in development. Where construction began on the stage of ideas, planning, program development activities, budgeting , procurement of resources to the implementation of a more emphasis on real desire or the real needs of the community in a group of people.  Integrated Community Development (ICD) is a place that is focused on the integrated delivery of education, health, youth training, and economic empowerment of community-based integrated manner. With Mustahik Relation Officer (MRO) as human resources assistant, ICD became the center of the distribution of the program so that the program is more scalable, and controlled. Keywords: Zakat Fund, Empowerment, and Poor Urban.